Inequalities in youth citizenship knowledge: Do language abilities of classroom peers matter? - Eidhof, Bram; Ten Dam, Geert; Dijkstra, Anne Bert; van de Werfhorst, Herman (JSSE - Journal of Social Science Education, 2022)
Keywords: citizenship competence, language, compositional effects, primary education Highlights: Is acquiring individual citizenship knowledge also associated with peer language environment? Students in classes with lower language achievement attain higher civic knowledge scores High language-achievement students do better if part of lower language achievement class Students with lower achievement level do better when part of a better performing class Also the variance in language skills in the class influences citizenship knowledge Purpose: The degree to which inequalities in citizenship outcomes of students develop, may depend on the composition of the classroom. We investigate to what degree language competences of the students’ class mates are associated with youth citizenship knowledge. Design/methodology/approach: A Dutch nationally representative data was used. Given the nested structure of the data, multilevel analyses were performed. Findings: Inequalities in citizenship knowledge may be reduced when low language ability students are surrounded with classroom peers who display both variation in and high average levels of language ability. Being surrounded with high language ability peers was shown to have a negative general effect on citizenship knowledge of lower performing students, in line with the big-fish-little-pond effect. Research limitations/implications: Before recommending our findings as a basis for policy-making within schools, additional evidence must be gathered to establish the causal nature of the relationships suggested by our analyses.